Therapeutic Effect and Mechanism of Bushen-Jianpi-Jiedu Decoction Combined with Chemotherapeutic Drugs on Postoperative Colorectal Cancer - Yang, Meng-Die; Zhou, Wen-Jun; Chen, Xiao-Le; Chen, Jian; Ji, Qing; Li, Qi; Wang, Wen-Hai; Su, Shi-Bing (Frontiers in Pharmacology, 2021)
There is a lack of effective therapeutic drugs in patients with postoperative colorectal cancer (PCRC). This study was aim to investigate the therapeutic effect and mechanism of Bushen-Jianpi-Jiedu Decoction combined with chemotherapy on PCRC with liver and kidney yin deficiency and spleen deficiency syndrome (LKYD-SDS) by made analysis of clinical therapy data, integrative analysis of RNA-seq and Label-free data, analysis of network pharmacology and in vitro pharmacological experimental verification. In the assessment of clinical therapy, the median progression-free survival (PFS) and Karnofsky performance score (KPS) were increased in PCRC patients by BSJPJDD combined with chemotherapy treatment for 3 months, compared to chemotherapy alone (P<0.05). The analysis of RNA-seq and Label-free combined with network pharmacology showed that 559 DEGs and 11 DEPs were potential targets, which involved in the regulation of multiple signaling pathways, such as MAPK, PI3K-Akt and HIF-1 signaling pathway. In the experimental verification, ELISA assay showed that plasma ZEB2, CAT and KRT78 were decreased, IL-1Α, CD5L, FBLN5, EGF and KRT78 were increased by above comparison (P<0.05). Furthermore, the cell viability was inhibited by BSJPJDD combined with oxaliplatin and the expressions of p-ERK1/2 and p-ERK1/2 and ERK1/2 ratio were up-regulated in SW620 cells compared to BSJPJDD or oxaliplatin alone (P<0.001). These data suggested that BSJPJDD combined with chemotherapy prolongs the survival and improves quality of life of PCRC patients with LKYD-SDS, and may be associated with the regulation of MAPK/ERK signaling pathway.